(untitled) (Journal of Environmental Bioremediation and Toxicology, 2025)
Reactive dyes are one of the most common dyes used in fabric re-dyeing; as such, their indiscriminate discharge into the environment is causing serious pollution in urban Kano, Nigeria. This research was aimed at assessing the potential of fungal species isolated from one of the major dyeing sites in Kano: Kofar Na’isa dyeing pit for the remediation of reactive dyes. The fungal species (Aspergillus striatus NEF4, Candida tetrigidarum NRRL Y-48142 1, Fusarium equiseti SPF466, and F. oxysporum FusCic45B) were isolated and identified from the dye-contaminated soil using dilution plating, pour plate, streak culture techniques, and DNA analysis. The isolated organisms were used to assess their bioremediation potential through biosorption and biodecolourisation of dye wastewater. The highest dye removal efficiency through biomass biosorption and enzymatic action was recorded after 48 hours, at pH 11.3 and a temperature of 37 °C. The dye removal by biosorption and biodecolourisation was within the ranges of 19.7 – 86.9% and 58.9 – 71.4% for A. straitus, 23.9 – 84.4% and 50.6 – 80.8% for C. tetrigidarum, 18.3 - 97.9% and 47.7 - 86.7% for F. equiseti, respectively. However, F. oxysporum displayed a negative biosorption but achieved 53.6 – 90.2% colour removal by enzymatic action. Dye removal increased with an increase in contact time due to gradual mycelial absorption. The isolated fungal species have proven to be effective in the remediation of reactive dyes, and thus, can be employed in regulating environmental contamination caused by dyes.